Diagnostic value and risk correlation of serum heart-type fatty acid-binding protein (H-FABP) and osteoprotegerin (OPG) in chronic heart failure - Zheng, Weifeng; Liu, Mingda; Xu, Sanduo; Xu, Wang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the value of H-FABP and OPG in determining severity of heart function in those suffering from long-term heart failure.Method: 196 patients with persistent heart failure who were admitted to our hospital between June 2023 and October 2024 were chosen. A comparison was made between the three groups of chronic heart failure patients' general clinical information, H-FABP, and OPG levels. The associations between OPG and H-FABP and various clinical forms of chronic heart failure, heart failure severity, and measurement markers related to echocardiography were examined. To assess NT-proBNP, H-FABP, and OPG detection alone and in combination for HFrEF and HFpEF in order to determine their diagnostic utility. Following their discharge, all patients were monitored for three to six months. Results: There was a positive correlation (r=0.61) between H-FABP and the NYHA classification, LA (r=0.46), LV (r=0.51), HS-TnT (r=0.31), NT-proBNP (r=0.58), SUA (r=0.38), etc., and negatively correlated with the LVEF (r=-0.76), NT-proBNP (r=0.49), etc., and negatively correlated with the LVEF (r=-0.60) (P
Keywords: Osteoprotegerin; NT-proBNP; Chronic disease; Cardiac function; Sensitivity analysis